1999
DOI: 10.1038/sj.leu.2401511
|View full text |Cite
|
Sign up to set email alerts
|

CD79b expression in B cell chronic lymphocytic leukemia: its implication for minimal residual disease detection

Abstract: The surface expression of CD79b, using the monoclonal antibody (Mab) CB3-1, on B lymphocytes from normal individuals and patients with B cell chronic lymphocytic leukemia (CLL) has been analyzed using triple-staining cells for flow cytometry. In addition, the clinical significance of CD79b expression in CLL patients and its possible value for the evaluation of minimal residual disease (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…We found that from all flow cytometric approaches tested, only the four-color immunophenotype CD19 þ CD5 þ CD43 þ CD20 low was 100% specific for CLL in comparison to ASO IgH RQ-PCR up to a maximum sensitivity of 2.2E-4. Surprisingly, in spite of the upregulation of CD5 on benign B cells after SCT (our unpublished data and demonstrated before 46,47 ), CD19 þ CD5 þ CD20 low remained a specific threecolor immunophenotype for CLL cells (2.2% false positive samples). Moreover, CD19 þ CD5 þ CD20 low proved to be slightly more sensitive than CD19 þ CD5 þ CD43 þ CD20 low and considerably more sensitive than CD19 þ CD43 þ CD20 low .…”
Section: Figurementioning
confidence: 69%
“…We found that from all flow cytometric approaches tested, only the four-color immunophenotype CD19 þ CD5 þ CD43 þ CD20 low was 100% specific for CLL in comparison to ASO IgH RQ-PCR up to a maximum sensitivity of 2.2E-4. Surprisingly, in spite of the upregulation of CD5 on benign B cells after SCT (our unpublished data and demonstrated before 46,47 ), CD19 þ CD5 þ CD20 low remained a specific threecolor immunophenotype for CLL cells (2.2% false positive samples). Moreover, CD19 þ CD5 þ CD20 low proved to be slightly more sensitive than CD19 þ CD5 þ CD43 þ CD20 low and considerably more sensitive than CD19 þ CD43 þ CD20 low .…”
Section: Figurementioning
confidence: 69%
“…37 This was not observed at the protein level in the current work. The explanation may be that the extracellular epitope of CD79b is not necessarily expressed, 38 despite the presence of the pertinent mRNA species. 39 In conclusion, our results revealed a large group of CLL surface membrane antigens with a heterogeneous expression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it imposes to know beforehand the type of light chain expressed at diagnosis on malignant cells for a given patient. Other antibodies such as CD20, CD79b, CD22, and CD43 have demonstrated their usefulness in the characterization of CLL cells and MRD evaluation and more recent fourcolor flow cytometry studies have reported an increased sensitivity of their detection down to the expected threshold of 10 À4 (23)(24)(25)(26)(27). These approaches are universal as they can be used for every patient and allow for a simple straightforward and recommended single-step labeling followed by lysis-no-wash on a small volume of whole blood of about 100 lL (28).…”
Section: à3mentioning
confidence: 99%